2020
DOI: 10.1002/agj2.20085
|View full text |Cite
|
Sign up to set email alerts
|

Narrow rows and high maize plant population improve water use and grain yield under conservation agriculture

Abstract: The relationship between maize (Zea mays L.) population density and grain yield is influenced by soil and crop management strategies, including Conservation Agriculture (CA). However, little is known about the response of maize grain yield to varying plant population and/or row spacing under CA. A 3-yr study was conducted under CA to evaluate the effects of plant population and row spacing on maize grain yield, plant available soil water, and soil temperature. Plant populations ranging from 40,000 to 80,000 pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Maintaining distance of row to row and plant to plant is an important factor in the cultivation of crops as it significantly influences the growth and development of crops by ensuring efficient utilization of resources [47]. Proper spacing provides better vegetative growth as well as rooting, it also reduces the risks of disease incidence by reducing excessive humidity and weeds which may serve as a host.…”
Section: Effect Of Spacing On Growth and Yield Of Maizementioning
confidence: 99%
“…Maintaining distance of row to row and plant to plant is an important factor in the cultivation of crops as it significantly influences the growth and development of crops by ensuring efficient utilization of resources [47]. Proper spacing provides better vegetative growth as well as rooting, it also reduces the risks of disease incidence by reducing excessive humidity and weeds which may serve as a host.…”
Section: Effect Of Spacing On Growth and Yield Of Maizementioning
confidence: 99%
“…the so-called Argentinean system) (Smith et al , 2019. Haarhoff and Swanepoel (2020) reported on the effect of higher plant populations on the yield of maize grown in trials in the Eastern Free State. They found significant increases in maize yield with increasing plant density, the second year showed similar trends, but the results were not significantly different.…”
Section: Major Findings About Commercial Farmers In the Ca Fip Projec...mentioning
confidence: 99%
“…They found that the grain yields were highest for NTR, followed by TR, NR, and CR across all planting densities, and that total biomass production had the same response as the grain production. In South Africa, Haarhoff and Swanepoel [18] conducted research with 40,000 to 80,000 plants ha −1 planted at 0.5, 0.76 and 1 m row spacings to evaluate the effects of row spacing on yields under conservation agriculture. Higher yields were achieved at high plant populations and wide row spacings, and they concluded larger plant populations have higher water use and extract more water from the soils than smaller populations, reducing the plant-available water.…”
Section: Twin Rows-positive Responsesmentioning
confidence: 99%